2019
DOI: 10.1021/acsami.9b10920
|View full text |Cite
|
Sign up to set email alerts
|

pKa-Directed Incorporation of Phosphonates into MOF-808 via Ligand Exchange: Stability and Adsorption Properties for Uranium

Abstract: We report a class of pK a -directed, precise incorporation of phosphonate ligands into a zirconium-based metal−organic framework (Zr-MOF), MOF-808, via ligand exchange. By replacing of formate ligands with methylphosphonic acid (MPA), ethanephosphonic acid (EPA), and vinylphosphonic acid (VPA), whose pK a values are slightly higher than that of the benzenetricarboxylic acid (BTC) linker in MOF-808, daughter MOFs can be synthesized without controlling the stoichiometric amounts of added MPA. The methylphosphona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(55 citation statements)
references
References 71 publications
4
51
0
Order By: Relevance
“…On the other side, Pal et al [79] reported the isoelectric point of GG close to 2.2: GG in acidic conditions may be considered neutral, while in mild acid conditions the biopolymer turns negatively charged. The first ionization constant of phosphonic acids depends on the side chain bound to phosphorus; however, for short chains the pK a values are close to 2.4 [80]. It means that GG and phosphonate groups have similar acid behavior, while chitosan is bringing base properties (associated with amine groups).…”
Section: Ph Effectmentioning
confidence: 98%
“…On the other side, Pal et al [79] reported the isoelectric point of GG close to 2.2: GG in acidic conditions may be considered neutral, while in mild acid conditions the biopolymer turns negatively charged. The first ionization constant of phosphonic acids depends on the side chain bound to phosphorus; however, for short chains the pK a values are close to 2.4 [80]. It means that GG and phosphonate groups have similar acid behavior, while chitosan is bringing base properties (associated with amine groups).…”
Section: Ph Effectmentioning
confidence: 98%
“…We also note that the experimentally measured lattice constants might be affected by residual water within the MOF-808 framework. 11,31 Therefore, we examined the effect of water on physical properties of MOF-808. Several water-containing models were constructed by adding water molecules to the tetrahedral cage of model I and then re-optimized using DFT methods in CP2K.…”
Section: Mof-808 and Gas Adsorptionmentioning
confidence: 99%
“…1.2 % (w/w) incorporation with minimal DCA leakage, as determined by ICP‐OES, postsynthetic loading of drugs containing metal‐binding units resulted in partial or total displacement of DCA (Table S1), as determined by 1 H NMR spectroscopic analysis of acid‐digested samples, suggesting their loading occurs through attachment to the Zr positions (subsequently detaching DCA ) rather than pore storage (see SI, Section S3.1 for full characterisation). AL loading resulted in a complete structural change, likely due to the affinity of its phosphonate groups for Zr inducing breakdown, again confirming the competing coordination of the drugs. As such, this postsynthetic process was not considered viable for multiple drug loading.…”
Section: Resultsmentioning
confidence: 65%
“…1 DCA per 3 BDC) whilst IBU/DCA@UiO‐66 showed a smaller degree of incorporation of IBU (2.9 mol % compared to BDC) due to its higher p K a , and similarly ≈37 mol % of DCA . Alendronate had the highest incorporation, again likely representative of its ditopicity and the Zr‐phosphonate affinity, as AL/DCA@UiO‐66 contained 38.1 mol % (ca. 1 AL per 2.5 BDC), suggesting its possible role as a linker, and 18.8 mol % of DCA (ca.…”
Section: Resultsmentioning
confidence: 99%